(2E,2'E)-3,3'-(1,4-Phenylene)bis[1-(4-fluorophenyl)- prop-2-en-1-one] - Chidan Kumar, C. S.; Ching, Kheng Quah; Chandraju, S.; Lokanath, N. K.; Naveen, S.; Abdoh, Muneer (International Union of Crystallography, 2017)
The title bis-chalcone compound, C24H16F2O2, crystallizes with one halfmolecule in the asymmetric unit. The molecule lies about an inversion centre at the centroid of the central benzene ring. The olefinic double bonds adopt E conformations. In the crystal, C—H...O hydrogen bonds form sheets of molecules in the ac plane and C—H...F hydrogen bonds form zigzag chains along the a-axis direction. These combine to generate a three-dimensional network of molecules stacked along the c-axis direction.